Future Studies: Its Epistemology and its Impact to Human Civilization - Prof. Dr. I. Bambang Sugiharto; Drs. Fabianus Sebastian Heatubun, SLL. (Extension Course Filsafat ( ECF ), 2020)
Future Studies: Its Epistemology and its Impact to Human Civilization